PENINGKATAN POPULASI PAKAN ALAMI Daphnia sp DENGAN MEDIA AMPAS TAHU DAN EKSTRAK JAHE PADA KOMPOSISI YANG BERBEDA - Safitri, Nanda Ayu; Firmani, Ummul; Aminin, Aminin (Journal of Aquatropica Asia, 2024)
Daphnia sp is a small aquatic organism that is rich in nutrients and is generally used as a potential natural food because of its high nutritional content. Challenges in fish farming arise because the availability of Daphnia sp is not always stable. As an alternative solution, tofu dregs and ginger extract are used as a source of protein and nutrition for Daphnia sp. Tofu dregs contain protein from soybean starch, while ginger extract contains immunostimulants. This study aims to evaluate the population density and growth rate of Daphnia sp by using media with tofu dregs and ginger extract with certain variations in composition. This research was carried out in Gopaan Sembunganyar Dukun-Gresik Hamlet in April-May 2024. The research method used was an experimental approach with a Completely Randomized Design (RAL), consisting of 3 treatments which were repeated 3 times, so that a total of 9 experimental units were obtained. Each treatment used a water volume of 8 liters with a Daphnia density of 20 individuals per liter. The parameters observed were temperature, pH, amonia, protein, fat and carbohydrate concentrations. The research results showed that the activity of providing Tofu Dregs and Ginger Extract had a significant influence on population density and growth of Daphnia sp. Treatment P2 showed the highest results with a density reaching 2653 ind.Lˉ¹, growth rate of 33.17%, protein content of 33.17%, fat content of 8.99%, and carbohydrate content of 53.36%. Keywords: Tofu dregs, Daphnia sp, ginger extract, growth, natural food